2017
DOI: 10.3390/rs9070739
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Temporal X-Band Radar Interferometry Using Corner Reflectors: Application and Validation at the Corvara Landslide (Dolomites, Italy)

Abstract: Abstract:From the wide range of methods available to landslide researchers and practitioners for monitoring ground displacements, remote sensing techniques have increased in popularity. Radar interferometry methods with their ability to record movements in the order of millimeters have been more frequently applied in recent years. Multi-temporal interferometry can assist in monitoring landslides on the regional and slope scale and thereby assist in assessing related hazards and risks. Our study focuses on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 69 publications
(73 reference statements)
1
25
0
Order By: Relevance
“…Multitemporal interferometric techniques like small baseline subsets (SBAS) and persistent scatter interferometric SAR (PSInSAR) are useful methods known to help with the above-mentiond issues [38,39]. Multiple studies have shown the practicality of these processing techniques as they relate to deformation monitoring [40][41][42][43]. Studies by Calabro et al [44] and Dai et al [45] each use different methods to account for the phase delay that is caused by the SAR waves' propagation through the atmosphere/ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Multitemporal interferometric techniques like small baseline subsets (SBAS) and persistent scatter interferometric SAR (PSInSAR) are useful methods known to help with the above-mentiond issues [38,39]. Multiple studies have shown the practicality of these processing techniques as they relate to deformation monitoring [40][41][42][43]. Studies by Calabro et al [44] and Dai et al [45] each use different methods to account for the phase delay that is caused by the SAR waves' propagation through the atmosphere/ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…These study results match better with CR9's velocity results than CR8's, confirming the assumption of a more accurate estimate in descending path than in ascending path. The maximum offset is indeed obtained on a short time interval in ascending images (2017-10-01/2017- [10][11][12][13][14][15][16][17][18][19]. The pairs with the smallest velocity uncertainty are obtained with CR9 (2017-09-30/2018-07-09 and 2017-11-17/2018-07-15), since they represent the longest time intervals.…”
Section: Dates Time Interval (D) Velocity (Cm/d) Direction Differencementioning
confidence: 88%
“…Satellite SAR data used in this special issue include archived ERS and Envisat ASAR [1], ALOS/PALSAR [2,3], COSMO-SkyMed constellation [4], TerraSAR-X [5], TerraSAR-X/TanDEM-X [6], and Sentinel-1 [7]. In addition, "Envisat 2010+" data, which started on 22 October 2010 and lasted until the communication with the Envisat satellite was suddenly lost on 8 April 2012, were involved.…”
Section: Sarmentioning
confidence: 99%
“…A complex earthflow with spatially varying displacement patterns over Corvara landslides in the Italian Alps was assessed using 16 artificial corner reflectors installed on the source, track and accumulation zones of the landslide, based on multi-temporal X-band COSMO-SkyMed constellation imagery [4]. The satellite observations were validated by differential GPS time-series data and proved to be a promising method for monitoring landslides characterized by linear and relatively slow movement rates [4]. GB-InSAR was applied to track the rapid movement of earth flows over the Capriglio landslide in northern Appennines, Italy, which was re-activated in April 2013 [9].…”
Section: Landslide Deformation Monitoringmentioning
confidence: 99%